EVIDENCE OF A BLOOD PRESSURE REDUCTION DURING THE COVID-19 ASSOCIATED LOCKDOWN: A PLAUSIBLE EXPLANATION FOR THE OBSERVED DECLINES IN ACUTE CARDIOVASCULAR DISEASES?. (April 2021) - Girerd, Nicolas; Meune, Christophe; Duarte, Kevin; Vercamer, Vincent; Lopez-Sublet, Marilucy; Mourad, Jean-Jacques
Abstract : Objective: The Covid-19 pandemic has been associated with a marked reduction in the incidence of cardiovascular diseases. The main objective of the study was to quantify the changes in blood pressure (BP) and heart rate (HR) prior to and after initiation of the lockdown. Design and method: A big data analysis of BP and HR measurements recorded during the lockdown period versus measurements during the Covid-19 period prior to confinement as well as versus measurements recorded in 2019. All participants were from the Paris urban area. Subjects used a Withings connected home blood pressure monitor and had at least one measurement prior to and during the lockdown and in 2019. Results: A total of 297, 089 BP recordings were available from 2273 participants (age 56.3 ± 12.8 years, 81.1% male). Recording frequency was similar before and during the lockdown. BP gradually decreased during the first 4 weeks of confinement, reaching a decrease of 3 mmHg (-2.4 to -3.9) in systolic BP (SBP) and 1.5 mmHg (-1.4 to -2.2) in diastolic BP (DBP) from week 4 to week 7 (all p < 0.001). Age and sex-adjusted comparisons yielded similar results. Participants with higher SBP and DBP had a greater decrease in SBP and DBP during the lockdown (p < 0.0001 each); age and gender had no significant effect. No significant variation in HR was detected during the studied periods. Figure. No caption available. Conclusions: Our study demonstrates a progressive decrease in SBP and DBP during the lockdown that may partly explain the concomitant reported reduction in the incidence of acute cardiovascular diseases.